Talent development in sport: Moving beyond nature and nurture - Baker, J.; Young, B. W. (Talent identification and development in sport. International perspectives, 2021)
While debates about the factors explaining human nature can be traced to ancient Greece, the scientific study of human achievement began with Francis Galton's studies of exceptional scientists, musicians, politicians and athletes (among others) in the mid-1800s (Galton, 1869). What made Galton's work unique compared to the work of others such as Descartes or Hume was his capacity to create empirical tools and frameworks to explore what, until then, were philosophical arguments. This marked a major turning point in discourse in this area, undoubtedly helped by significant changes occurring in biology (Darwin's publication of The Origin o f Species in 1859) and psychology (Wundt and James beginning in 1862, and 1890, respectively). One of Galton's most lasting contributions (for good or ill) was his suggestion that the factors affecting human achievement can be divided into those exerting their influence through biological mechanisms (i.e., through 'nature') and those exerted through leaming and experience (i.e., through 'nurture'). Galton (1869) came down firmly on the side of nature: 'There is a definite limit to the muscular powers of every man, which he cannot by any education or exertion overpass' (pp. 14-15). On the sesquicentennial of his work, however, most scientists currendy believe achievement works through a dynamic and complex interaction of genetic and environmental factors. In this chapter, we explore the historical evolution of the nature versus nurture debate, particularly in sport, before highlighting evidence for an interactionist perspective. Understanding the foundations of this debate will help scientists, coaches and athletes develop a more informed understanding of the range of influences affecting hum an performance and sporting achievement.